Influence of the menstrual cycle on compression-induced pain during mammography: correlation with the thickness and volume of the mammary gland - Kitaoka, Hitomi; Kawashima, Hiroko (Radiological physics and technology, 2018)
In mammography, breast compression is necessary and an important factor influencing image quality. The purpose of this study was to determine the influence of the menstrual cycle on compression-induced pain during mammography and to evaluate the association between the thickness and volume of the mammary gland and pain. We examined basal body temperature and categorized the menstrual cycle into five phases. We executed breast compression in the craniocaudal view using a customized compression plate, to which we introduced an opening. We measured the thickness of the mammary gland under compression using echography. Immediately after releasing the compression, we evaluated pain using the visual analogue scale. We performed magnetic resonance imaging (MRI) on the same day and measured the volume of the mammary gland. The thickness of the mammary gland, pain, and the volume of the mammary gland were minimal in the late follicular phase and maximal in the late luteal and early follicular phases. It was shown that the changes in the thickness and volume of the mammary gland during the menstrual cycle accounted for the changes in compression-induced pain. On MRI examination of each breast quadrant, the same changes were observed in areas A and C. In area A, it was shown that both the anatomical characteristics and the increase in volume of the mammary gland were associated with pain. We concluded that the late follicular phase constitutes the optimal timing for mammography.